Hidrolisados parciais de soro proteínas lácteas bovina e bubalina obtidos com proteases imobilizadas: ensaios de transporte e absorção de peptídeos através das técnicas da dialisabilidade e cultura de células caco-2 - Bassan, Juliana Cristina [UNESP] (2015)
Proteases are important industrial enzymes with wide range of application. They catalyze the hydrolysis of proteins and are widely exploited in the production of protein hydrolysates from milk protein (casein and whey), soy and fish, generating high value-added products. In this work, trypsin (EC 3.4.21.4) and pepsin (EC 3.4.23.1) were immobilized on a low cost alternative support, corn cob powder (CCP) to obtain partial hydrolysates of bovine and buffalo cheese whey, the main by-product of the dairy industry. The pretreated support was activated with glyoxyl and IDA-glyoxyl groups (trypsin) and glutaraldehyde (trypsin and pepsin). The derivatives showed immobilization yields higher than 80% and 90% for trypsin and pepsin, respectively, and recovered activities higher than 85% for trypsin derivatives and 94% for pepsin derivative. The derivative trypsin-glyoxyl-CCP showed excellent thermal stability at 65 ° C, which was 1111 times higher that obtained with free enzyme, followed by derivative trypsin-IDA-glyoxyl-CCP (900-fold) and trypsin-glutaraldehyde-CCP (5.38-fold). For the derivative pepsin-glutaraldehyde-CCP the thermal stability was held at 45 ° C and was 1.42 times greater than the free enzyme. Stabilized derivatives trypsin-glyoxyl-CCP and pepsin-glutaraldehyde-CCP were used in a packed bed reactor for the hydrolysis of bovine and buffalo cheese whey. The relationship derivative/working volume was 1:2 and the process was conducted at 45 ° C with a flow of 10.1mL/h. For the hydrolysis, bovine and buffalo cheese whey were dialyzed and treated with kaolin to reduce lactose and fats, respectively. The hydrolysates were fractionated by gel filtration chromatography (Sephadex G25) to obtain 5kDa peptide pools. The transport and absorption of each peptide pools were evaluated by in vitro methods simulating the gastrointestinal digestion/dialysability and by Caco-2 cell ...